Information Access Evaluation -- Multilinguality, Multimodality, and Interaction 5th International Conference of the CLEF Initiative, CLEF 2014, Sheffield, UK, September 15-18, 2014, Proceedings - Kanoulas, Evangelos; Lupu, Mihai; Clough, Paul; Sanderson, Mark; Hall, Mark; Hanbury, Allan; Toms, Elaine (Information Systems and Applications, incl. Internet/Web, and HCI, 2014)
This book constitutes the refereed proceedings of the 5th International Conference of the CLEF Initiative, CLEF 2014, held in Sheffield, UK, in September 2014. The 11 full papers and 5 short papers presented were carefully reviewed and selected from 30 submissions. They cover a broad range of issues in the fields of multilingual and multimodal information access evaluation, also included are a set of labs and workshops designed to test different aspects of mono and cross-language information retrieval systems.